Preliminary Evaluation of Possible Radiological Risks Arising from Floods in Rio Grande do Sul in 2024 (Brazilian Journal of Radiation Sciences, 2024)
In May 2024, extensive flooding impacted multiple cities in Rio Grande do Sul, Brazil, including the capital, Porto Alegre. This research evaluates the potential radiological and nuclear hazards resulting from these floods. 106 facilities that use radioactive materials in nearby regions were identified, of which 30 are located in the regions of interest, categorized based on IAEA risk standards. The flooding compromised containment and monitoring systems, heightening the risk of exposure to various hazardous materials, including radioactive substances. The floods affected high-risk sites in São Leopoldo and Canoas and moderate-risk sites in Porto Alegre and São Leopoldo. The study underscores the necessity of enhancing disaster preparedness and response systems to safeguard public health and the environment.
Keywords: flood; radiological risk; radiation safety; natural disasters; environmental contamination